Imaging artifacts of nonadhesive liquid embolic agents in conventional and cone-beam CT in a novel in vitro AVM model - Schmitt, Niclas; Floca, Ralf; Paech, Daniel; El-Shafie, Rami; Neuberger, Ulf; Bendszus, Martin; Möhlenbruch, Markus Alfred; Vollherbst, Dominik (Clinical neuroradiology, 2021)
Background A major drawback of liquid embolic agents (LEAs) is the generation of imaging artifacts (IA), which may represent a crucial obstacle for the detection of periprocedural hemorrhage or subsequent radiosurgery of cerebral arteriovenous malformations (AVMs). This study aimed to compare the IAs of Onyx, Squid and PHIL in a novel three-dimensional in vitro AVM model in conventional computed tomography (CT) and cone-beam CT (CBCT). - Methods Tubes with different diameters were conﬁgured in a container resembling an AVM with an artiﬁcial nidus at its center. Subsequently, the AVM models were ﬁlled with Onyx 18, Squid 18, PHIL 25% or saline and inserted into an imaging phantom (n = 10/LEA). Afterwards CT and CBCT scans were acquired. The degree of IAs was graded quantitatively (Hounsﬁeld units in a deﬁned region of interest) and qualitatively (feasibility of deﬁning the nidus)—Onyx vs. Squid vs. PHIL vs. saline, respectively. - Results Quantitative density evaluation demonstrated more artifacts for Onyx compared to Squid and PHIL, e.g. 48.15 ± 14.32 HU for Onyx vs. 7.56 ± 1.34 HU for PHIL in CT (p < 0.001) and 41.88 ± 7.22 density units (DU) for Squid vs. 35.22 ± 5.84 DU for PHIL in CBCT (p = 0.044). Qualitative analysis showed less artifacts for PHIL compared to Onyx and Squid in both imaging modalities while there was no difference between Onyx and Squid regarding the deﬁnition of the nidus (p > 0.999). - Conclusion In this novel three-dimensional in vitro AVM model, IAs were higher for the EVOH/tantalum-based LEAs Onyx and Squid compared to iodine-based PHIL. Onyx induced the highest degree of IAs with only minor differences to Squid.
Gesehen am 04.09.2023